2016
DOI: 10.1186/s13063-016-1447-5
|View full text |Cite
|
Sign up to set email alerts
|

No improvement in the reporting of clinical trial subgroup effects in high-impact general medical journals

Abstract: BackgroundWhen subgroup analyses are not correctly analyzed and reported, incorrect conclusions may be drawn, and inappropriate treatments provided. Despite the increased recognition of the importance of subgroup analysis, little information exists regarding the prevalence, appropriateness, and study characteristics that influence subgroup analysis. The objective of this study is to determine (1) if the use of subgroup analyses and multivariable risk indices has increased, (2) whether statistical methodology h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…A proposal by Kent and colleagues offers a framework for assessing and reporting multivariate risk‐based heterogeneity in treatment effects that can be applied to a wide variety of conditions . Although this framework has yet to be applied widely , there is increasing support for updating the conventional methods for evaluating treatment efficacy in order to appreciate the known heterogeneity in clinical trials . The manner in which data are presented and interpreted is vital to understanding variability in response and may help differentiate statistically significant findings from clinically meaningful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A proposal by Kent and colleagues offers a framework for assessing and reporting multivariate risk‐based heterogeneity in treatment effects that can be applied to a wide variety of conditions . Although this framework has yet to be applied widely , there is increasing support for updating the conventional methods for evaluating treatment efficacy in order to appreciate the known heterogeneity in clinical trials . The manner in which data are presented and interpreted is vital to understanding variability in response and may help differentiate statistically significant findings from clinically meaningful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The problem caused by the unbalanced groups can be minimized by using multivariate analyses that include the most relevant factors associated with the benefit. This would be the best method for performing subgroup analysis; unfortunately, it is little used, or studies that used it are not published …”
Section: What's Known and Objectivementioning
confidence: 99%
“…An increasing number of publications perform subgroup analyses without detailed evaluation . Our easy‐to‐use checklist allows assessment of reliability and applicability of subgroup analyses that my help in the comprehensive evaluation of drugs and health interventions.…”
Section: ‘What's New?’ and Conclusionmentioning
confidence: 99%
“…regarding the conduct, reporting, and interpretation of subgroup analyses in clinical trials [9e12]. Recent studies found that there has been no improvement in the reporting of subgroup analyses [13,14], and that there were discrepancies between subgroup analyses planned in protocols and journal publications of clinical trials [15]. Many journals have been accepting and publishing clinical trial protocols so as to promote public access to them [16,17].…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%